A Critical Review of Alcohol Administration Guidelines in Laboratory Medication Screening Research: Is It Time to Include Treatment Seekers?. (20th December 2020) - Roberts, Walter; Verplaetse, Terril L.; Ramchandani, Vijay A.; McKee, Sherry A.
Abstract : Human laboratory studies play an important role in alcohol use disorder (AUD) medication development. Medications that are found to be safe and effective during human laboratory screening will then move to more expensive clinical trials in patient populations. Given the gatekeeping role of human laboratory studies in the medication development pipeline, it is critical that these studies accurately forecast how pharmacotherapies will perform under true‐to‐life clinical conditions. On the other hand, the design of these studies also must adhere to ethical guidelines: certain aspects of clinical reality cannot be incorporated into screening studies because doing so might place the participant at risk for harm or breach other ethical guidelines. Conventions exist that guide the resolution of these conflicting ideals. This article considers the practice of recruiting non–treatment‐seeking heavy drinkers to participate in laboratory screening studies. By convention, volunteers are excluded from laboratory screening studies that involve alcohol administration if they are deemed "treatment seeking, " meaning that they recently stopped drinking or are motivated to do so. Although this common practice may reduce risk to participants, findings may not accurately predict medication effects on treatment seekers. Indeed, there is empirical evidence that treatment seekers differ from nontreatment seekers in their responses to medications ( Neuropsychopharmacology 2017a; 42: 1776; Am J Drug Alcohol Abuse 2017b; 43: 703; J Psychiatr Res 2006; 40: 383). Here, we argue for the importance of recruiting treatment seekers for this research due to their qualitative difference from nontreatment seekers. We argue that these individuals should be the default population in human laboratory medication screening studies. We conclude by discussing 2 case examples of medication experiments led by our research groups that involved administering medications to treatment seekers. Abstract : This flowchart highlights a case example of a pharmacotherapy screening study in which treatment‐seeking heavy drinkers received alcohol in the laboratory. We specifically recruited heavy‐drinking individuals who reported interest in cutting down on their alcohol use. After completing the laboratory session, participants attended weekly treatment sessions with a licensed clinical psychologist with expertise in the treatment of alcohol misuse. Numerous safeguards were integrated into the protocol to reduce the risk associated with alcohol administration in this population.